When a Stone Tries to Climb up a Slope: The Interplay between Lexical and Perceptual Animacy in Referential Choices - Vogels, Jorrig; Krahmer, Emiel; Maes, Alfons (Frontiers in Psychology, 2013)
Several studies suggest that referential choices are influenced by animacy. On the one hand, animate referents are more likely to be mentioned as subjects than inanimate referents. On the other hand, animate referents are more frequently pronominalized than inanimate referents. These effects have been analyzed as effects of conceptual accessibility. In this paper, we raise the question whether these effects are driven only by lexical concepts, such that referents described by animate lexical items (e.g. ‘toddler’) are more accessible than referents described by inanimate lexical items (e.g. ‘shoe’), or can also be influenced by context-derived conceptualizations, such that referents that are perceived as animate in a particular context are more accessible than referents that are not. In two animation-retelling experiments, conducted in Dutch, we investigated the influence of lexical and perceptual animacy on the choice of referent and the choice of referring expression. If the effects of animacy are context-dependent, entities that are perceived as animate should yield more subject references and more pronouns than entities that are perceived as inanimate, irrespective of their lexical animacy. If the effects are tied to lexical concepts, entities described with animate lexical items should be mentioned as the subject and pronominalized more frequently than entities described with inanimate lexical items, irrespective of their perceptual animacy. The results show that while only lexical animacy appears to affect the choice of subject referent, perceptual animacy may overrule lexical animacy in the choice of referring expression. These findings suggest that referential choices can be influenced by conceptualizations based on the perceptual context.